2008
DOI: 10.3201/eid1409.071382
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices regarding Avian Influenza (H5N1), Afghanistan

Abstract: From February through April 2007, avian influenza (H5N1) was confirmed in poultry in 4 of 34 Afghan provinces. A survey conducted in 2 affected and 3 unaffected provinces found that greater knowledge about reducing exposure was associated with higher socioeconomic status, residence in affected provinces, and not owning backyard poultry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 6 publications
4
29
0
Order By: Relevance
“…The present study also showed that about 50% respondents had moderate practices. Almost similar level of practices was also reported in a study in Myanmar, Afghanistan and Thailand among the high-risk people (MMRD Research Services, Myanmar 2006; (Leslie et al, 2008). A good number (73%) of the respondents practiced hand washing after handling birds, 13.7% used separate foot wear and 7% of the respondents used gloves.…”
Section: Results and Discussion Socio-demographic Characteristics Of supporting
confidence: 52%
“…The present study also showed that about 50% respondents had moderate practices. Almost similar level of practices was also reported in a study in Myanmar, Afghanistan and Thailand among the high-risk people (MMRD Research Services, Myanmar 2006; (Leslie et al, 2008). A good number (73%) of the respondents practiced hand washing after handling birds, 13.7% used separate foot wear and 7% of the respondents used gloves.…”
Section: Results and Discussion Socio-demographic Characteristics Of supporting
confidence: 52%
“…Parallel to the results reported from a study in Europe, which also included Turkey, people appear to have a limited understanding of how avian influenza in their region should influence their consumption patterns (Eurobarometer 2006). Similar to the finding in Afghanistan (Leslie et al 2008) and the Lao People's Democratic Republic (Barennes et al 2007), our study suggests that conventional education and behavioural change messages have a limited effect in populations with highest exposure.…”
Section: Discussionsupporting
confidence: 75%
“…Gaps in knowledge about transmission and treatment were also evident in our study and resulted in anticipated risky behaviours during an outbreak. Another study about bird flu from Afghanistan reported that level of knowledge was far lower amongst persons with lower socioeconomic status (Leslie et al 2008), and gaps in knowledge about avian influenza, especially about humanto-human transmission and prevention, have been reported in other studies, too (Abbate et al 2006;Di Giuseppe et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Although more than 12 million chickens are reared in Afghanistan, the majority (98%) are raised in house backyards and fed on scraps, with little or no proper husbandry. However, only a few hundred birds were infected with H5N1 and no outbreaks had been reported from the commercial facilities [12]. Education of owners and breeders on the safe handling of birds, restriction of movement and importation bans were set to prevent virus transmission.…”
Section: Influenza Surveillance and Influenza-like Illnessmentioning
confidence: 99%